2020
DOI: 10.1097/cm9.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metabolic syndrome on short-term outcome of carotid revascularization: a large sample size study in Chinese population

Abstract: Background Metabolic syndrome (MetS) is relatively common worldwide and an important risk factor for cardiovascular diseases. It is closely linked to arterial stiffness of the carotid artery. However, the association of MetS with the safety of carotid revascularization has been rarely studied. The aim of this study was to observe the current status of MetS and its components in Chinese carotid revascularized patients, and investigate the impact on major adverse clinical events (MACEs) after caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results of our study are of even greater relevance in the context in which the rates of 30-day stroke/death after CEA in asymptomatic patients with insulin-dependent DM exceeded international vascular societies' guideline thresholds for acceptable outcomes in asymptomatic patients, especially those with anatomic high-risk criteria [ 9 ]. General metabolic syndrome was also a risk for short-term MACCEs after CEA, but not CAS, in a 2000-chinese cohort reported by Jiao et al [ 22 ]. However, it must be admitted that these data come from a retrospective, observational study, and our analysis did not differentiate between insulin-dependent diabetics and noninsulin-dependent diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are of even greater relevance in the context in which the rates of 30-day stroke/death after CEA in asymptomatic patients with insulin-dependent DM exceeded international vascular societies' guideline thresholds for acceptable outcomes in asymptomatic patients, especially those with anatomic high-risk criteria [ 9 ]. General metabolic syndrome was also a risk for short-term MACCEs after CEA, but not CAS, in a 2000-chinese cohort reported by Jiao et al [ 22 ]. However, it must be admitted that these data come from a retrospective, observational study, and our analysis did not differentiate between insulin-dependent diabetics and noninsulin-dependent diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few MS diagnostic criteria commonly used internationally are stricter criteria for blood pressure and blood sugar, and the use of waist circumference instead of BMI. The circulatory system of the whole body is a whole, and the damage to blood vessels caused by MS is widespread [11,12]. At present, there are no su cient clinical trials to provide evidence for whether routine screening of intracranial blood vessels, neck blood vessels, coronary arteries and blood vessels of both lower limbs is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In the control group, the rs2479409 was associated with a lower risk of metabolic syndrome, a low risk of having increased alkaline phosphatase >p75, and a low risk of increased gamma-glutamyltranspeptidase. Several reports have shown that metabolic syndrome increases the risk of cardiovascular events [ 45 , 46 , 47 ]. Recent studies have suggested that an increased serum alkaline phosphatase is a predictor of cardiovascular disease and vascular calcification [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%